Individual-tree basal area growth models for jack pine and black spruce in northern Ontario - Zhang, Lianjun; Peng, Changhui; Dang, Qinglai (The Forestry Chronicle, 2004)
Individual-tree models of five-year basal area growth were developed for jack pine (Pinus banksiana Lamb.) and black spruce (Picea mariana (Mill.) BSP) in northern Ontario. Tree growth data were collected from long-term permanent plots of pure and mixed stands of the two species. The models were fitted using mixed model methods due to correlated remeasurements of tree growth over time. Since the data covered a wide range of stand ages, stand conditions and tree sizes, serious heterogeneous variances existed in the data. Therefore, the coefficients of the final models were obtained using weighted regression techniques. The models for the two species were evaluated across 4-cm diameter classes using independent data. The results indicated (1) the models of jack pine and black spruce produced similar prediction errors and biases for intermediate-sized trees (1228 cm in tree diameter), (2) both models yielded relatively large errors and biases for larger trees (> 28 cm) than those for smaller trees, and (3) the jack pine model produced much larger errors and biases for small-sized trees (< 12 cm) than did the black spruce model. Key words: mixed models, repeated measures, model validation

Developing and Evaluating Tree Height-Diameter Models at Three Geographic Scales for Black Spruce in Ontario - Peng, Changhui; Zhang, Lianjun; Zhou, Xiaolu; Dang, Qinglai; Huang, Shongming (Northern Journal of Applied Forestry, 2004)
Abstract A total of 11,612 black spruce trees were measured from permanent sample plots across the boreal and central regions of Ontario and were used to fit the well-known Chapman-Richards growth model at provincial, regional, and ecoregional scales. The results suggest that the height-diameter relationships of black spruce vary with different geographic regions and scales. There were significant variations in height-diameter relationships for black spruce between boreal and central regions as well as among some of the seven ecoregions. The ecoregion-based height-diameter models presented here will provide more accurate predictions for tree height and, consequently, tree volume than these models developed at both provincial and regional scales. Furthermore, the heterogeneity of tree species should be considered in developing and applying ecoregion-based height-diameter models for predicting local tree height.

A component object model strategy for reusing ecosystem models - Liu, Jinxun; Peng, Changhui; Dang, Qinglai; Apps, Mike; Jiang, Hong (Computers and Electronics in Agriculture, 2002)

Developing carbon-based ecological indicators to monitor sustainability of Ontario’s forests - Peng, Changhui; Liu, Jinxun; Dang, Qinglai; Zhou, Xiaolu; Apps, Mike (Ecological Indicators, 2002)

TRIPLEX: a generic hybrid model for predicting forest growth and carbon and nitrogen dynamics - Peng, Changhui; Liu, Jinxun; Dang, Qinglai; Apps, Michael J; Jiang, Hong (Ecological Modelling, 2002)

Historic carbon budgets of Ontario’s forest ecosystems - Liu, Jinxun; Peng, Changhui; Apps, Mike; Dang, Qinglai; Banfield, Edwin; Kurz, Werner (Forest Ecology and Management, 2002)